2014
DOI: 10.2139/ssrn.2519503
|View full text |Cite
|
Sign up to set email alerts
|

The Panzar-Rosse Revenue Test and Market Power in Banking

Abstract: The Panzar-Rosse H statistic is a commonly used measure of market power in banking. It is widely believed that H > 0 is inconsistent with significant market power. This study rigorously disproves that perception. Instead, the possibility of H > 0 under conditions of substantial market power turns out robust to the timing of banks' actions, relative costs, choice of strategic variable, degree of product differentiation, strategy (static or dynamic), and degree of heterogeneity in banks' conduct (collusive versu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 73 publications
0
4
1
Order By: Relevance
“…Hence, Spierdijk and Shaffer (2015) who derived these for the case when H > 0 (whereas our results suggest ≤ 0).…”
Section: Datacontrasting
confidence: 64%
See 1 more Smart Citation
“…Hence, Spierdijk and Shaffer (2015) who derived these for the case when H > 0 (whereas our results suggest ≤ 0).…”
Section: Datacontrasting
confidence: 64%
“…However, they concluded that an appropriately specified revenue equation can be used to test the degree of market power using the sign of H. Spierdijk and Shaffer (2015) demonstrated that H > 0 is not inconsistent with substantial market power as the traditional interpretation suggested and cautioned over such an interpretation of the H-statistic. However, our results show that ≤ 0 and is therefore not in the H > 0 category.…”
Section: Models With and Without Assetsmentioning
confidence: 99%
“…All of these different assessments of the degree of competition are consistent in suggesting that the Vietnamese system operated under monopoly during the 1999 -2009 period. This provides a robustness that makes this inference convincing and should help reduce any concerns that there are exceptions to the standard interpretation of the Panzar-Rosse H-statistic that can call into question inferences based upon it -see Spierdijk and Shaffer (2015).…”
Section: Resultsmentioning
confidence: 84%
“…Bikker et al (2012) discussed the problems associated with interpreting H according to these rules. However, they concluded that an appropriately specified revenue equation can be used to test the degree of market power using the sign of H Spierdijk and Shaffer (2015). demonstrated that H > 0 is not inconsistent with substantial market power as the traditional interpretation suggested and cautioned over such an interpretation of the H-statistic.…”
mentioning
confidence: 99%
“…Bikker et al (2012) prove that a negative H-statistic does not necessarily indicate a monopoly even though the equilibrium test indicates long-run equilibrium. They argue that the H-statistic jointly measures competitive conduct and long-run structural equilibrium and, to evaluate its applicability, additional information is needed about costs, market equilibrium, and even market demand elasticity (see also Shaffer, 2004a andShaffer, 2015). Therefore, we also analyze competition in the clearing and settlement industry by estimating the Lerner index and Boone indicator.…”
Section: Technological Developmentmentioning
confidence: 99%